2015
DOI: 10.3389/fpls.2015.00543
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of inflorescence architecture in legumes

Abstract: The architecture of the inflorescence, the shoot system that bears the flowers, is a main component of the huge diversity of forms found in flowering plants. Inflorescence architecture has also a strong impact on the production of fruits and seeds, and on crop management, two highly relevant agronomical traits. Elucidating the genetic networks that control inflorescence development, and how they vary between different species, is essential to understanding the evolution of plant form and to being able to breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 118 publications
1
93
0
2
Order By: Relevance
“…The growth habit is a crucial determinant of plant architecture and plays a key role in influencing various seed and pod yield component traits in chickpea as well as adaptation of its plant-type to diverse agroecological environments. The plant growth habit is thus a complex yield contributing quantitative trait and usually governed by convoluted interplay of multiple genes/QTLs (quantitative trait loci) especially regulating diverse developmental processes in chickpea (Benlloch et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The growth habit is a crucial determinant of plant architecture and plays a key role in influencing various seed and pod yield component traits in chickpea as well as adaptation of its plant-type to diverse agroecological environments. The plant growth habit is thus a complex yield contributing quantitative trait and usually governed by convoluted interplay of multiple genes/QTLs (quantitative trait loci) especially regulating diverse developmental processes in chickpea (Benlloch et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Within the legumes, the value of a comparative approach to candidate gene identification has led to the characterization of the molecular identity of TFL1 co-orthologs such as FIN in common bean (designated as PvTFL1y ; Repinski et al, 2012); Dt1 in soybean ( GmTFL1 ; Tian et al, 2010); and DETERMINATE ( DET ; PsTFL1a ) and LATE FLOWERING ( LF ; PsTFL1c ) in pea (Foucher et al, 2003; Weller and Ortega, 2015). Recent findings have clearly shown that in several legume species, determinate inflorescence architecture is conferred by mutation of specific TFL1 genes (Benlloch et al, 2015). The determinate growth habit caused by mutations within specific TFL1 -homologs in other grain legumes indicates that the determinate function is conserved in these species (Kong et al, 2010; Tian et al, 2010; Kwak et al, 2012; Repinski et al, 2012; Dhanasekar and Reddy, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Decades of research in model and crop species have revealed genetic pathways that dictate the reproductive transition to flowering and the development of diverse inflorescence forms Tanaka et al 2013;Kyozuka et al 2014;Benlloch et al 2015). Upon perception and integration of environmental and endogenous cues, such as day length and the flowering hormone florigen (Benlloch et al 2007;Shalit et al 2009), meristems gradually mature from a small flat structure into a large domed reproductive inflorescence meristem (IM) (Kwiatkowska 2008).…”
mentioning
confidence: 99%